Development of reference assignment in children: a direct comparison to the performance of cognitive shift - Murakami, Taro; Hashiya, Kazuhide (Frontiers in Psychology, 2014)
The referent of a deictic embedded in a particular utterance or sentence is often ambiguous. Reference assignment is a pragmatic process that enables the disambiguation of such a referent. Previous studies have demonstrated that receivers use social-pragmatic information during referent assignment; however, it is still unclear which aspects of cognitive development affect the development of referential processing in children. The present study directly assessed the relationship between performance on a reference assignment task (Murakami and Hashiya, in preparation) and the dimensional change card sort task (DCCS) in 3- and 5-years-old children. The results indicated that the 3-years-old children who passed DCCS showed performance above chance level in the event which required an explicit (cognitive) shift, while the performance of the children who failed DCCS remained in the range of chance level; however, such a tendency was not observed in the 5-years-old, possibly due to a ceiling effect. The results indicated that, though the development of skills that mediate cognitive shifting might adequately explain the explicit shift of attention in conversation, the pragmatic processes underlying the implicit shift, which requires reference assignment, might follow a different developmental course.